Virtual Reality as a Tool for Enhancing Understanding of Tactical Urbanism - Italo Seghetto; Ricardo Lopes; Fernando Lima (Architecture, 2025)
Tactical urbanism (TU) and Virtual Reality (VR) both aim to reimagine physical spaces, with TU utilizing rapid, temporary, scalable, and cost-effective physical interventions to test and refine urban design, while VR offers immersive virtual environments for exploration and analysis. This article investigates the integration of VR with TU to address challenges in effectively communicating and evaluating temporary urban interventions. This study is grounded in a literature review on spatial perception, TU, and VR, followed by an empirical experiment involving Brazilian college students. Participants interacted with a parklet installation in both physical and virtual environments, with their spatial perception and emotional responses evaluated using the AR4CUP (Augmented Reality for Collaborative Urban Planning) protocol. The results demonstrated that VR positively impacts the perception, usability, and social dynamics of urban spaces. Participants emphasized the importance of social interaction and recreational activities, reinforcing VR’s potential to simulate and refine urban interventions. A crucial avenue for future research is identifying best practices for using VR as a platform for collaborative design and decision-making. This step could enhance VR’s effectiveness in creating public spaces that align with community needs, fostering participatory planning and promoting inclusive, functional, and enriching environments.